CANDI PARI SEBAGAI SUMBER BELAJAR SEJARAH SISWA SEKOLAH MENENGAH ATAS DI SIDOARJO - Aulia Fitriany; Satrio Wibowo; Wahyu Sudrajad (Biro 3 Kemahasiswaan dan Kerjasama Universitas Abduracman Saleh Situbondo, 2026)
The background of this research is the Pari Temple as one of the historical sites in Sidoarjo Regency that can serve as a source for learning History. The purpose of this research is to describe the role of the Pari Temple as a source of historical learning, as well as to understand the students' responses. The research method used is descriptive qualitative method. Data collection is conducted through interviews with students, teachers, and the management of the Pari Temple. Field observations are made to observe student interactions during visits to the Pari Temple. Questionnaires are given to students to ascertain their responses. The validity of the data is ensured through data triangulation by comparing the results of interviews, observations, and questionnaires to ensure the accuracy of the obtained information. The research results show that Candi Pari as a learning resource is a cultural heritage rich in historical values, possesses architectural value, and can be used as a source of historical learning. Based on the research results, it can be concluded that Candi Pari is an effective learning resource in history education.